2020
DOI: 10.14309/ctg.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Marked Elevation of Lipase in COVID-19 Disease: A Cohort Study

Abstract: INTRODUCTION: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing the pandemic of coronavirus disease 2019 (COVID-19) is a global health crisis. Possible pancreatic involvement has recently been observed in these patients; however, its significance is unclear. The aim of this study was to evaluate the association of significantly elevated lipase with disease outcomes. METHODS: Data about demographics, symptoms, laboratory values, and clinical outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 19 publications
6
80
3
Order By: Relevance
“…[ 36 ] (China) 9/52 (17.3%) 7/52 (13.5%) 5/52 (9.6%) None .. 4/9 (44.4%) 7/9 patients - corticosteroids; No definite clinical AP Barlass et al . [ 37 ] (USA) 14/83 (16.8%) .. 14/83 (16.8%) None .. 13/14 (92.9%) Elevated lipase associated with increased ICU admission and intubation COVID-19 Coronavirus disease 2019; CT Computed tomography; NSAIDs Non-steroidal anti-inflammatory drugs; GI Gastrointestinal; ULN Upper limit of normal; AP Acute pancreatitis; ICU Intensive care unit. …”
Section: Real World Data Of Covid-19 and Pancreatic Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…[ 36 ] (China) 9/52 (17.3%) 7/52 (13.5%) 5/52 (9.6%) None .. 4/9 (44.4%) 7/9 patients - corticosteroids; No definite clinical AP Barlass et al . [ 37 ] (USA) 14/83 (16.8%) .. 14/83 (16.8%) None .. 13/14 (92.9%) Elevated lipase associated with increased ICU admission and intubation COVID-19 Coronavirus disease 2019; CT Computed tomography; NSAIDs Non-steroidal anti-inflammatory drugs; GI Gastrointestinal; ULN Upper limit of normal; AP Acute pancreatitis; ICU Intensive care unit. …”
Section: Real World Data Of Covid-19 and Pancreatic Injurymentioning
confidence: 99%
“…Laboratory abnormalities suggestive of pancreatic injury have been noted in 8.5%–17.3% of cases [ 15 , [34] , [35] , [36] , [37] ] in various studies. Overall 51 (12.8%) of the 397 reported patients had pancreatic injury.…”
Section: Real World Data Of Covid-19 and Pancreatic Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Barlass et al 10 . from Chicago, USA, studied 294 admitted COVID‐19 patients, and 83 of them were checked for serum lipase.…”
Section: The Phenomenon Of Increased Serum Amylase And/or Lipase In Cmentioning
confidence: 99%
“…Novel insights were provided by Barlass et al 10 . They studied the serum lipase level and found that elevated serum lipase level was significantly related to the rate of ICU admission and intubation.…”
Section: Increased Serum Amylase And/or Lipase In Covid‐19: Critical mentioning
confidence: 99%